A scholarly roundtable part II Bérénice Reynaud: 'The love of cinema is also the love of encountering people'. Issue 2 (2nd September 2021) - Reynaud, Bérénice
ABSTRACT: A roundtable discussion organized by the JCC's two guest co-editors, Timmy Chih-Ting Chen and Belinda Qian He, took place between early December 2020 and January 2021. Scholars from a variety of backgrounds and co-founders of two remarkable cinephilic organizations/groups (Deep Focus and DIRECT UBE) in the Chinese-speaking world were invited to share their experiences and ideas about cinema and cinephilia. The roundtable started with a virtual gathering via zoom, which initially took a roundtable form. Ten participants from six time zones continued the conversation through contributing to a Google document. The shared file afforded each participant the opportunity to partake at their own convenience, thereby enabling the roundtable to develop organically during two months. The online format thus shaped a timely attempt to experiment with the notion of roundtable during the pandemic. Divided into two parts, the roundtable revolved around how participants discussed their multiple identities, positionalities, and border-crossing experiences about cinema. Among them, Bérénice Reynaud stands out as a special guest who shared and reflected on her personal experiences as a non-Chinese and non-Chinesespeaking scholar, curator, and cinephile who has developed close connections with Chineselanguage cinemas. As the second part of the roundtable, Bérénice Reynaud's autobiographical account is shown below.